(untitled) (Journal of the College of Basic Education, 2023)
Ceramic nano-ferrite series of the formula MnFe2-xSmxO4 (x=0, 0.5,and0.1) is prepared,usingsolution combustion process. XRD-analysis showed poorly resolved patternsof as-burnt powders which are progressively mended by progressive raising of heat treatment temperature.TEM particle-size analysis indicated that thedimensions of the as-burnt powder is of the nano-order. Moreover, thermal analysis of these powders exhibited a continuous decline in the TG-curve in the temperature range of up to 1000C.On the other hand no explicit reaction was detectable in the behavior of the DTA-curveof the as-burnt ferrite powder for the same range.Room temperaturemagnetization measurements of green compacted or sintered powders of various compositions, confirmed thesuperparamagnetic nature of the nano-ferrites. However, modifications are observed in hysteresis loops when various ferrite powders are subjected to the above mentioned heat treatmentschemes. This may be attributed to variations in atomic order (inversion of the spinel structure) , also the partial replacement of Fe-ions by rare earth Sm-ions may induce local strains, impurities, or lattice defects which may also cause such modifications .On the other hand,values of magnetic parameters like permeability and remnant magnetization are explicitly altered upon Fe-ion replacement or heat treatments.